Case Report: Neonatal Diabetes Mellitus Caused by a Novel GLIS3 Mutation in Twins - London, Shira; De Franco, Elisa; Elias-Assad, Ghadir; Barhoum, Marie Noufi; Felszer, Clari; Paniakov, Marina; Weiner, Scott A.; Tenenbaum-Rakover, Yardena (Frontiers in Endocrinology, 2021)
Background: Mutations in GLIS3 cause a rare syndrome characterized by neonatal diabetes mellitus (NDM), congenital hypothyroidism, congenital glaucoma and cystic kidneys. To date, 14 mutations in GLIS3 have been reported, inherited in an autosomal recessive manner. GLIS3 is a key transcription factor involved in β-cell development, insulin expression, and development of the thyroid, eyes, liver and kidneys. Cases: We describe non-identical twins born to consanguineous parents presenting with NDM, congenital hypothyroidism, congenital glaucoma, hepatic cholestasis, cystic kidney and delayed psychomotor development. Sequence analysis of GLIS3 identified a novel homozygous nonsense mutation, c.2392C>T, p.Gln798Ter (p.Q798*), which results in an early stop codon. The diabetes was treated with a continuous subcutaneous insulin infusion pump and continuous glucose monitoring. Fluctuating blood glucose and intermittent hypoglycemia were observed on follow-up. Conclusions: This report highlights the importance of early molecular diagnosis for appropriate management of NDM. We describe a novel nonsense mutation of GLIS3 causing NDM, extend the phenotype, and discuss the challenges in clinical management. Our findings provide new areas for further investigation into the roles of GLIS3 in the pathophysiology of diabetes mellitus.